X-Ray computed tomography in biomedical engineering - Cierniak, Robert (Springer, 2011)
Computed Tomography gives a detailed overview of various aspects of computed tomography. It discusses X-ray CT tomography from a historical point of view, the design and physical operating principles of computed tomography apparatus, the algorithms of image reconstruction and the quality assessment criteria of tomography scanners. Algorithms of image reconstruction from projections, a crucial problem in medical imaging, are considered in depth. The author gives descriptions of the reconstruction methods related to tomography scanners with a parallel X-ray beam, trough solutions with fan-shaped beam and successive modifications of spiral scanners. Computed Tomography contains a dedicated chapter for those readers who are interested in computer simulations based on studies of reconstruction algorithms. The information included in this chapter will enable readers to create a simulation environment in which virtual tomography projections can be obtained in all basic projection systems. This monograph is a valuable study on computed tomography that will be of interest to advanced students and researchers in the fields of biomedical engineering, medical electronics, computer science and medicine.